Determination of Heavy Metals in Effluent / Wan Mohd Tarmizi bin Wan Mohd Yusuf - Wan Mohd Yusuf, Wan Mohd Tarmizi (2013)
The objective of this research project is to determine the concentration of 5 toxic metals from industrial effluent.The five metal elements are cadmium (Cd), lead (Pb), copper (Cu), nickel (Ni), and iron(Fe).Two sources of effluent have been taken for the analysis of heavy metals concentration. It is very important to monitor the concentration of toxic metals effluent whether the concentrations are safe to be released to the environment or need to be treated. A serious contamination to human life and environment can occur if there is no observation on the effluent that will be released to the environment. The sample of effluent used in this work are different from each others depending on their source. The sample preparation need to carefully done to avoid external contamination and loss of target elements. The analysis of heavy metals were performed using AAS and later confirmed by ICP-MS. The results indicate that the effluent have been treated to fit the requirement from Malaysia Enviromental Act.